2020
DOI: 10.3390/ijerph17061992
|View full text |Cite
|
Sign up to set email alerts
|

Bus Workers’ Experiences with and Perceptions of a Health Promotion Program: A Qualitative Study Using a Focus Group Discussion

Abstract: We conducted a focus group discussion with bus workers to evaluate their experiences and perceptions, as well as their reasons for participating in a program for vulnerable workers. The study also sought to identify the strengths and weaknesses of the program. A total of nine bus workers participated in the focus group discussion. The focus group discussion was conducted based on a semi-structured guide, which was developed from discussions among the researchers and a review of major preliminary studies. The v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A previous investigation reported approximately 40% of MTA transit workers had one or more underlying health problems 40 . Previous studies have also indicated bus and subway operators are at higher risk for cardiovascular diseases and abdominal obesity compared with the general population 11,16,23,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous investigation reported approximately 40% of MTA transit workers had one or more underlying health problems 40 . Previous studies have also indicated bus and subway operators are at higher risk for cardiovascular diseases and abdominal obesity compared with the general population 11,16,23,41 …”
Section: Discussionmentioning
confidence: 99%
“…40 Previous studies have also indicated bus and subway operators are at higher risk for cardiovascular diseases and abdominal obesity compared with the general population. 11 , 16 , 23 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Quantitative research, which focuses on hypothesis validation, such as the superiority of specific treatments or the effectiveness of specific policies, and the generalization of findings, has been the primary research methodology in the field of healthcare. Qualitative research has been mostly applied for studies such as subjective disease experiences and attitudes with respect to health-related patient quality of life [10][11][12], experiences and perceptions regarding the use of healthcare services [13][14][15], and assessments of the quality of care [16,17]. Moreover, qualitative research has focused on vulnerable populations, such as the elderly, children, disabled [18][19][20], minorities, and socially underprivileged with specific experiences [21,22].…”
Section: Applications Of Qualitative Research and Its Usefulness In T...mentioning
confidence: 99%